2011
DOI: 10.1016/j.jvs.2011.01.061
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of straight and Venaflo-type cuffed arteriovenous ePTFE grafts in an animal study

Abstract: The results of the present study confirm the inferior clinical results of ePTFE grafts used for hemodialysis access. Although the patency rates of cuffed grafts were superior, in both graft types a significant pseudointima leading to subtotal graft stenosis was observed in all grafts. Both straight and Venaflo-grafts. The Venaflo grafts have a slightly bettertype cuffed ePTFE grafts have major hemodynamic drawbacks that have to be addressed in future graft design efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…In a CFD study using a pulsatile circuit in a silastic model, the Venaflo™ graft created a significantly lower WSS and a more homogenous flow pattern at the graft-vein anastomosis compared to a straight graft (5). An animal study supported this potentially beneficial hemodynamic effect on the development of NIH; however, a high incidence of pseudo-intima formation was observed within the cuff leading to early graft dysfunction (6). Several retrospective analyses and randomized clinical trials (RCTs) comparing either the Venaflo™ graft or a PTFE graft with autologous venous cuff with a standard PTFE graft have been conducted; however, with modest results (7–12).…”
Section: Graft Geometry and Flow Modulationmentioning
confidence: 98%
See 2 more Smart Citations
“…In a CFD study using a pulsatile circuit in a silastic model, the Venaflo™ graft created a significantly lower WSS and a more homogenous flow pattern at the graft-vein anastomosis compared to a straight graft (5). An animal study supported this potentially beneficial hemodynamic effect on the development of NIH; however, a high incidence of pseudo-intima formation was observed within the cuff leading to early graft dysfunction (6). Several retrospective analyses and randomized clinical trials (RCTs) comparing either the Venaflo™ graft or a PTFE graft with autologous venous cuff with a standard PTFE graft have been conducted; however, with modest results (7–12).…”
Section: Graft Geometry and Flow Modulationmentioning
confidence: 98%
“…In one study, the Venaflo™ graft demonstrated a decrease in NIH formation (12). The lack of a beneficial effect on patency of the Venaflo™ graft can possibly be attributed to pseudo-intima formation in its cuff, which has been described in a Venaflo™ porcine model (6). It is hypothesized that a flow separation caused by the large mainstream-to-wall angle of the expanding cuff favors thrombus formation (6, 13).…”
Section: Graft Geometry and Flow Modulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Antiplatelet treatment, anticoagulation and statin therapy have not shown real benefit in improving long-term graft patency (1622). Changing the graft configuration by using cuffed grafts, carbon-lined grafts and polyurethane grafts has shown no improvement in outcome and neither has graft tapering (2328).…”
Section: Innovations In Graft Compositionmentioning
confidence: 99%
“…The poor long-term prognosis of prosthetic grafts generally results from the development of intimal hyperplasia and consequent stenosis at the graft-vein anastomosis. 911 Prospective studies have shown the efficacy and safety of covered stents in venous outflow. 12 However, as these PTFE grafts fail, many of these patients develop disadvantaged anatomy, primarily due to unsuitable venous anatomy.…”
Section: Introductionmentioning
confidence: 99%